Sky view factors estimation using a 3d-gis extension - Souza, Léa Cristina Lucas (2003)
The sky view factor indicates the relationship between the visible area of the sky and the area covered by urban structures. A method of sky view factors (SVF) estimation for urban analysis was developed and implemented in a Geographical Information System (GIS). In order to validate this tool, this paper presents a comparison of actual SVF with the results obtained by simulating the SVF in particular areas of a medium sized city with the developed tool. The simulation with this tool pointed out many advantages, such as: reliability; flexibility and ability to predict sky view factors in future scenarios.